2017
DOI: 10.1103/physrevb.96.094511
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectrum of thermal counterflow turbulence in superfluid helium-4

Abstract: Recent preliminary experiments (Marakov et al Phys. Rev. B 91, 094503 (2015)), using tripletstate He2 excimer molecules as tracers of the motion of the normal fluid, have shown that, in thermal counterflow turbulence in superfluid 4 He, small scale turbulence in the superfluid component is accompanied, above a critical heat flux, by partially-coupled large-scale turbulence in both fluids, with an energy spectrum proportional to k −m , where m is greater than the Kolmogorov value of 5/3. Here we report the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(76 citation statements)
references
References 29 publications
6
70
0
Order By: Relevance
“…The trace S j (R) ≡ α S αα j (R) is a measure of the kinetic energy of turbulent (normal or superfluid) velocity fluctuations on scale R. Recently, the streamwise normal velocity across a channel, v x (y, t) was measured using thin lines of the triplet-state He 2 molecular tracers created by a femptosecond-laser field ionization of He atoms 42 across the channel. This way, the transversal 2 nd -order structure functions 11,12 of the normal-fluid velocity differences S xx n (R y ) were obtained. Similarly, one can use two or more tracer lines, separated in the streamline direction x, to measure the longitudinal structure function S xx n (R x ) and even inclined structure function S xx n (R x , R y ).…”
Section: Velocity Structure Functionsmentioning
confidence: 99%
“…The trace S j (R) ≡ α S αα j (R) is a measure of the kinetic energy of turbulent (normal or superfluid) velocity fluctuations on scale R. Recently, the streamwise normal velocity across a channel, v x (y, t) was measured using thin lines of the triplet-state He 2 molecular tracers created by a femptosecond-laser field ionization of He atoms 42 across the channel. This way, the transversal 2 nd -order structure functions 11,12 of the normal-fluid velocity differences S xx n (R y ) were obtained. Similarly, one can use two or more tracer lines, separated in the streamline direction x, to measure the longitudinal structure function S xx n (R x ) and even inclined structure function S xx n (R x , R y ).…”
Section: Velocity Structure Functionsmentioning
confidence: 99%
“…provided the counterflow velocity ρv n /ρ s exceeds a small critical velocity v 0 . To illustrate agreement with σ G1 , we computed v 2 L 1/2 using values for γ (a temperature-dependent parameter relating L to v ns ), v 0 , and the parameter c 2 reported in the recent work of Gao et al [27,28], and we approximated the mean vortex line spacing ℓ = L −1/2 across the entire parameter space. Since the agreement between σ G1 and v 2 L 1/2 appeared to be reasonable, we can use measured G1 velocity fluctuations to represent v 2 L 1/2 , and apply Eqn.…”
Section: Experimental Measurement Of Cmentioning
confidence: 99%
“…(2) to calculate its average value across the imaging plane. We begin by obtaining values for ℓ, γ, and v 0 using our own apparatus, employing both flow visualization and second sound attenuation according to the procedures outlined by Gao et al [27]. The results for each temperature are tabulated in Table I.…”
Section: Experimental Measurement Of Cmentioning
confidence: 99%
“…Visualization experiments were performed to observe the normal-fluid flow [27][28][29][30]. Marakov et al visualized the velocity profile of the normal fluid by using He * 2 molecules [30], and the characteristic energy spectra were analyzed [31,32]. A particle tracking velocimetry (PTV) experiment provides insights on statistical properties and indicated that the velocity fluctuations of the normal fluid are anisotropic in contrast to classical fluid [33,34].…”
mentioning
confidence: 99%